PENGARUH PEMBERIAN KREDIT MODAL KERJA TERHADAP RENTABILITAS PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK. UNIT TANAH LEMO DI KEC. BONTOBAHARI KAB.BULUKUMBA - AM, Sanusi; Herman, Herman (Perpustakaan dan Penerbitan Unismuh Makassar, 2015)
This study aims to determine the magnitude of the effect of working capital loans to rentability At PT. Bank Rakyat Indonesia (Persero) Tbk Tanah Lemo Unit, Bonto Bahari Sub-district, Bulukumba Regency for the last five years, from fiscal year 2009 to 2013. Population in this research is all data concerning giving of working capital credit for debtor and financial statement data at PT. Bank Rakyat Indonesia (Persero) Tbk Tanah Lemo Unit, Bonto Bahari Sub-district, Bulukumba District, while the sample of this research is the data of working capital credit and the five years of financial report from 2009 to 2013. From the results of data analysis can be concluded that the provision of working capital credit positf effect on profitability at PT. Bank Rakyat Indonesia (Persero) Tbk Tanah Lemo Unit, Bonto Bahari Sub-district, Bulukumba District.